2005
DOI: 10.1093/jxb/eri279
|View full text |Cite
|
Sign up to set email alerts
|

The role of sugars in integrating environmental signals during the regulation of leaf senescence

Abstract: Although leaf senescence results in a loss of photosynthetic carbon fixation, the senescence-dependent release of nutrients, especially of nitrogen, is important for the growth of young leaves and for reproduction. Environmental regulation of senescence is therefore a vital factor in the carbon and nitrogen economy of plants. Leaf senescence is a highly plastic trait that is affected by a range of different environmental factors including light, nutrient supply, CO2 concentration, and abiotic and biotic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
290
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 386 publications
(317 citation statements)
references
References 69 publications
8
290
1
3
Order By: Relevance
“…Measurement of soluble sugar and amino acid amounts at the beginning and end of the day was a useful tool for sensing mild water deficit in stage I and the beginning of stage II, and starch amounts indicated the severity of stress during stage III, when rehydration is required for plant recovery and where these compounds are also indicative. The soluble sugar and amino acid amounts and daily balance acted contrary to one another, as stated by Wingler et al (2006) for senescence, which is induced by drought (Hsiao, 1973), and can be viewed as metabolic signals for physiological responses to drought (Farrar et al, 2000;Rolland et al, 2006). However, plant response to water deficit depends on an enormous number of plant traits at all levels of organization, from the molecular to the plant levels, and there is no universal trait for drought tolerance (Sinclair and Purcell, 2005), though depending on the species under study, a number of traits can be useful in the evaluation of drought tolerance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Measurement of soluble sugar and amino acid amounts at the beginning and end of the day was a useful tool for sensing mild water deficit in stage I and the beginning of stage II, and starch amounts indicated the severity of stress during stage III, when rehydration is required for plant recovery and where these compounds are also indicative. The soluble sugar and amino acid amounts and daily balance acted contrary to one another, as stated by Wingler et al (2006) for senescence, which is induced by drought (Hsiao, 1973), and can be viewed as metabolic signals for physiological responses to drought (Farrar et al, 2000;Rolland et al, 2006). However, plant response to water deficit depends on an enormous number of plant traits at all levels of organization, from the molecular to the plant levels, and there is no universal trait for drought tolerance (Sinclair and Purcell, 2005), though depending on the species under study, a number of traits can be useful in the evaluation of drought tolerance.…”
Section: Discussionmentioning
confidence: 95%
“…Many researchers have investigated the relation between CO 2 assimilation and end-products in bean (Castrillo, 1992) and others species (Quick et al, 1992;Farrar et al, 2000;Wingler et al, 2006), showing the important role of leaf soluble sugar amounts in the feedback regulatory mechanisms of photosynthesis. In addition, starch and amino acid biosynthesis, which are regulated by soluble sugar amounts, can also act as a secondary feedback regulatory mechanism of photosynthesis (Paul and Pellny, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In higher plants and green algae, photosynthetic carbon fixation is also reduced in response to nitrogen deprivation, and excess carbon is generally stored in molecular pools that contain little or no nitrogen. In higher plants, this is usually in the form of starch (Diaz et al, 2005;Wingler et al, 2006), and Peng et al (2007) described increased transcript levels of two genes involved in starch biosynthesis in Arabidopsis (Arabidopsis thaliana) under nitrogen starvation. In the fresh water green alga Chlamydomonas reinhardtii, on the other hand, excess carbon is reportedly directed to fatty acid biosynthesis (Wang et al, 2009;Moellering and Benning, 2010), and Miller et al (2010) found increased expression of genes involved in lipid biosynthesis in C. reinhardtii when nitrogen was not available.…”
Section: Interspecies Comparisonmentioning
confidence: 99%
“…In terms of the regulation of senescence, not only transcription factors and hormones but also altered plant sourcesink relationships and the accumulation of some specific metabolites such as sugars and amino acids have been suggested to regulate the timing and developmental progression of leaf senescence (Noodén, 1980;Yoshida, 2003;van Doorn, 2004;Wingler et al, 2006). However, there is still little known about the involvement of metabolites in controlling senescence.…”
mentioning
confidence: 99%